Antioxidant soybean tar Glyteer rescues T‐helper‐mediated downregulation of filaggrin expression via aryl hydrocarbon receptor. Issue 2 (6th December 2014) - Takei, Kenjiro; Mitoma, Chikage; Hashimoto‐Hachiya, Akiko; Uchi, Hiroshi; Takahara, Masakazu; Tsuji, Gaku; Kido‐Nakahara, Makiko; Nakahara, Takeshi; Furue, Masutaka
Abstract Soybean tar Glyteer (Gly) has been widely used for the treatment of various inflammatory skin diseases in Japan since 1924 as an alternative to coal tar remedy. Recently, coal tar has been shown to induce barrier repair in atopic dermatitis via aryl hydrocarbon receptor (AhR). In this study, we demonstrated that Gly activated AhR by inducing its cytoplasmic to nuclear translocation in keratinocytes. The AhR ligation by Gly was biologically active, with significant and dose‐dependent upregulation of CYP1A1 expression, which is a specific marker for AhR activation. Gly upregulated the expression of filaggrin in an AhR‐dependent manner because its enhancing effect was completely abrogated in AhR‐knockdown keratinocytes. T‐helper (Th)2 cytokines inhibited the expression of filaggrin; however, Gly completely restored the Th2‐mediated inhibition of filaggrin expression. Furthermore, Gly coordinately upregulated a series of epidermal differentiation complex genes, including involucrin, loricrin and hornerin. In addition, Gly exhibited potent antioxidant activity through the activation of nuclear factor‐erythroid 2‐related factor‐2 (Nrf2) and downstream antioxidant enzymes such as NAD(P)H:quinone oxidoreductase 1 (Nqo1), which actually inhibited the generation of reactive oxygen species in keratinocytes treated with tumor necrosis factor‐α or benzo[α]pyrene. In conclusion, antioxidant Gly rescues the downregulated expression of filaggrin (and plausibly other barrier proteins) in a Th2‐skewed milieu via AhR activation, which may partly explain its empirical anti‐inflammatory therapeutic effects.